Phyto-Pharmacology of Ziziphus jujuba Mill – A Plant Review - R.T., Mahajan; M.Z, Chopda (Pharmacognosy Reviews)
Herbs have always been the natural form of medicine in India. Medicinal plants have curative properties due to presence of various complex chemical substances of different composition which contain secondary metabolites such as alkaloids, flavonoids, terpenoids, saponin and phenolic compounds distributed in different parts of the plants. Ziziphus jujuba Mill, a member of the family Rhamnaceae, commonly known as Bor, is used traditionally as tonic and aphrodisiac and sometimes as Hypnotic-sedative and Anxiolytic, anticancer (Melanoma cells), Antifungal, Antibacterial, Antiulcer, Anti-inflammatory, Cognitive, Antispastic, Antifertility/contraception, Hypotensive and Antinephritic, Cardiotonic, Antioxidant, Immunostimulant, and Wound healing properties. It possesses allied compounds viz. Ascorbic acid, thiamine, riboflavin-bioflavonoids and Pectin A and various chemical substances like Mauritine-A; Amphibine-H; Jubanine-A; Jubanine-B; Mucronine-D and Nummularine-B. Sativanine-E. Frangufoline, Ziziphine-A to Q, betulinic acid colubrinic acid, alphitolic acid, 3-O-cis-p-coumaroylalphitolic acid, 3-O-transpcoumaroylalphitolic acid, 3-O-cis-p-coumaroylmaslinic acid, 3-O-trans-pcoumaroylmaslinic acid, oleanolic acid, betulonic acid, oleanonic acid, zizyberenalic acid and betulinic acid, jujubosides A, B, A1 B1 and C and acetyljujuboside B and the protojujubosides A, B and B1, saponin, ziziphin, from the dried leaves of Z. jujube - 3-O-a-L-rhamnopyranosyl (1-2)-aarabinopyranosyl-20-O- (2,3)-di-O-acetyl-a-L-rhamnopyranosyl jujubogenin. Saponin from leaves and stem are 3-O- ((2-O- alpha – D – furopyranosyl – 3-O- beta – D –glucopyranosyl) – alpha – L – arabinopyranosyl) jujubogenin and (6’’’-sinapoylspinosin, 6’’’-feruloylspinosin and 6’’’-p-coumaroylspinosin. The present review discusses photo-chemistry, pharmacology, medicinal properties and biological activities of Z. jujuba and its usage in different ailments.
Keywords: Antioxidant; Antibacterial; Anticarcinogenic; Phytochemistry; Ziziphus jujuba